Hambatan Petugas Kesehatan dalam Penanganan Preeklampsia - Rinda Intan Sari (NHM PRESS, 2023)
Preeclampsia is a multi-system disorder that requires early management so as able to reduce maternal morbidity and mortality. The role of all elements is needed, one of them are healthcare worker (nurse/midwife) in the comprehensive early detection of preeclampsia. However, preeclampsia and maternal mortality are still high. There are several things that still hinder both during handling and referral. The purpose of this study was to explore the barriers of health workers in the management of preeclampsia in puskesmas. The method used is qualitative research with a phenomenological approach. Nine participants in this study were taken from 3 Puskesmas Poned. Collecting data by in-depth interviews and using thematic analysis. The results of the study, such as (1)Not all drugs are available at the Puskesmas (2)The referral process is too long for emergency patients (3)There are differences in the procedure for giving MgSO4, the dose and route of administration (4)Not all health workers training on preeclampsia and maternal emergencies. It can be concluded that the management of preeclampsia carried out needs evaluate and improved due to the emergence of personal and technical obstacles. Suggestions from the results of the research include evaluating the implementation and training so that healthcare are competent.